CircWHSC1 Promotes Breast Cancer Progression by Regulating the FASN/AMPK/mTOR Axis Through Sponging miR-195-5p - Chen, Qian; Yang, Zhen; Ding, Hongjian; Li, Huaqing; Wang, Weiyu; Pan, Zhiyu (Frontiers in Oncology, 2022)
Numerous studies reveal that circular RNAs (circRNAs) affect cancer progression. CircWHSC1 is a novel circRNA that accelerates ovarian cancer progression. Nevertheless, the function of circWHSC1 in regulating breast cancer (BC) is elusive. Here, quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was carried out to detect the profiles of circWHSC1 and miR-195-5p in BC tissues and corresponding non-tumor tissues. Gain- and loss-of-function assays were implemented both in vivo and ex vivo to verify the significance of circWHSC1 in BC development. BC cell proliferation was estimated by the cell counting kit-8 (CCK-8) and BrdU assays. Transwell assay was implemented to test BC cell migration and invasion. The protein levels of FASN, AMPK and mTOR were determined by Western blot. Moreover, immunohistochemistry was performed to examine Ki67 and FASN expression. As shown by the result, circWHSC1 was up-regulated in BC tissues versus adjacent non-tumor tissues. circWHSC1 overexpression was correlated with higher tumor stages, lymphatic metastasis and worse survival of BC patients. Functionally, overexpressing circWHSC1 amplified proliferation, migration and invasion of BC cell lines and boosted xenograft tumor growth in nude mice. Bioinformatics uncovered that circWHSC1 functioned as a competitive endogenous RNA by sponging miR-195-5p, which was further corroborated by the dual-luciferase reporter assay and RNA immunoprecipitation. miR-195-5p delayed BC progression, which was dampened by circWHSC1 up-regulation. Fatty acid synthase (FASN) was affirmed as a direct target of miR-195-5p. miR-195-5p overexpression curbed FASN expression and activated its downstream AMPK pathway. Inhibition of FASN or activation of the AMPK pathway reversed circWHSC1-mediated oncogenic effects. Collectively, CircWHSC1 acted as an oncogene to expedite BC evolvement by modulating the miR-195-5p/FASN/AMPK/mTOR pathway.